2006
DOI: 10.1080/10717540500313398
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Polyvinyl Acetate Dispersion as a Sustained Release Polymer for Tablets

Abstract: Kollicoat SR 30D is a unique 30% aqueous dispersion of polyvinvyl acetate stabilized by polyvinyl-pyrrolidone intended for preparation of sustained release products. Detailed evaluation of this polymer dispersion as a sustained release coating for active pharmaceutical ingredients of two diverse classes of drugs was studied. A water insoluble drug (ibuprofen) and a water soluble drug (ascorbic acid) were selected as model active drugs. Ibuprofen was granulated using a GPCG-1 fluid bed processor prior to tablet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…1 The Expert Panel reviewed newly available studies since that assessment along with updated frequency and concentration of use information. 2 11 The Expert Panel confirmed that polyvinyl acetate is safe in the present practices of use and concentration given in Table 1 and did not reopen this safety assessment.…”
Section: Resultsmentioning
confidence: 92%
“…1 The Expert Panel reviewed newly available studies since that assessment along with updated frequency and concentration of use information. 2 11 The Expert Panel confirmed that polyvinyl acetate is safe in the present practices of use and concentration given in Table 1 and did not reopen this safety assessment.…”
Section: Resultsmentioning
confidence: 92%
“…Its major application is in membrane-controlled drug delivery systems [1][2][3][4][5][6][7] , but however, it has been successfully employed in matrix tablet preparation via fluidized-bed granulation 8 and spray drying 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of its high flexibility and low toxicity, polyvinyl acetate is widely used in the food industry as a base for chewing gum and for coating fruits and vegetables. From an environmental as well as economical point of view, aqueous-based systems are very much preferred over organic solvent-based systems [10,11]. Industrial applications of PVAc normally use it in the form of a liquefied emulsion.…”
mentioning
confidence: 99%